PEMBENTUKAN KARAKTER SISWA BERBASIS PENDIDIKAN SENI BUDAYA DI MAN 1 PALU - Syamsuddin Syamsuddin (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2019)
This research is titled ‘Forming Student Character Based on Cultural Arts Education at MAN 1 Palu’. The problems in this study are (1) What is the strategy of cultural arts-based character education in MAN 1 Palu, (2) What are the supporting and inhibiting factors of cultural arts-based character education at the level of senior high school education, (3) students, students, local education providers about the implementation and benefits of art and culture-based character education. The study was conducted at MAN 1 Palu with consideration (1) MAN 1 Palu was predicated as one of the schools active in the development of art and culture, (2) As an active school it turned out that it had many achievements both at the local and national level. The results of this research to show: (1) Art and cultural based character education in MAN 1 Palu using habituation methods, (2) Schools have character education bases that are highlighted, (3) Cultural arts subjects have been implemented in character education, (4) Education characters are not exclusive in cultural arts lessons but throughout subjects